Dynamic transition of chemolithotrophic sulfur-oxidizing bacteria in response to amendment with nitrate in deposited marine sediments - Aoyagi, Tomo; Kimura, Makoto; Yamada, Namiha; Navarro, Ronald R.; Itoh, Hideomi; Ogata, Atsushi; Sakoda, Akiyoshi; Katayama, Yoko; Takasaki, Mitsuru; Hori, Tomoyuki (Frontiers in Microbiology, 2015)
Although environmental stimuli are known to affect the structure and function of microbial communities, their impact on the metabolic network of microorganisms has not been well investigated. Here, geochemical analyses, high-throughput sequencing of 16S rRNA genes and transcripts, and isolation of potentially relevant bacteria were carried out to elucidate the anaerobic respiration processes stimulated by nitrate (20 mM) amendment of marine sediments. Marine sediments deposited by the Great East Japan Earthquake in 2011 were incubated anaerobically in the dark at 25°C for 5 days. Nitrate in slurry water decreased gradually for 2 days, then more rapidly until its complete depletion at day 5; production of N2O followed the same pattern. From day 2 to 5, the sulfate concentration increased and the sulfur content in solid-phase sediments significantly decreased. These results indicated that denitrification and sulfur oxidation occurred simultaneously. Illumina sequencing revealed the proliferation of known sulfur oxidizers, i.e., Sulfurimonas spp. and Chromatiales bacteria, which accounted for approximately 43.5% and 14.8% of the total population at day 5, respectively. They also expressed 16S rRNA to a considerable extent, whereas the other microorganisms, e.g., iron(III) reducers and methanogens, became metabolically active at the end of the incubation. Extinction dilution culture in a basal-salts medium supplemented with sulfur compounds and nitrate successfully isolated the predominant sulfur oxidizers: Sulfurimonas sp. strain HDS01 and Thioalkalispira sp. strain HDS22. Their 16S rRNA genes showed 95.2−96.7% sequence similarity to the closest cultured relatives and they grew chemolithotrophically on nitrate and sulfur. Novel sulfur-oxidizing bacteria were thus directly involved in carbon fixation under nitrate-reducing conditions, activating anaerobic respiration processes and the reorganization of microbial communities in the deposited marine sediments.